Instantaneous Pulsed-Light Cross-Linking of a Polymer Gate Dielectric for Flexible Organic Thin-Film Transistors - Kim, Soo Jin; Jang, Mi; Yang, Hee Yeon; Cho, Jinhan; Lim, Ho Sun; Yang, Hoichang; Lim, Jung Ah (American Chemical Society, 2017)
We report the instantaneous pulsed-light cross linking of polymer gate dielectrics on a flexible substrate by using intensely pulsed white light (IPWL) irradiation. Irradiation with IPWL for only 1.8 s of a poly(4-vinylphenol) (PVP) thin film with the cross-linking agent poly(melamine-co-formaldehyde) (PMF) deposited on a plastic substrate was found to yield fully cross linked PVP films. It was confirmed that the IPWL-cross-linked PVP films have smooth pinhole free surfaces and exhibit a low leakage current density, organic solvent, resistance; and good compatibility with organic semiconductor, and that they can be used as replacements for typical PVP dielectrics that are cross-linked with time and energy intensive thermal heating processes. The synchronization of the IPWL irradiation with substrate transfer was found to enable the preparation of cross-linked PVP films on large area substrates with a highly unifirm capacitance. Flexible OTFT based on IPWL-cross-linked PVP dielectrics were found to exhibit good electrical performance that is comparable to that of devices with thermally cross-linked PVP dielectric, as well as excellent deformation stability even at a bending radius of 3 mm.
Keywords: HIGH-PERFORMANCE; EFFICIENT PRODUCTION; FLASH; TEMPERATURE; NANOTUBES; POLYIMIDE